Students' evaluation of social studies teachers' effectiveness in selected junior secondary schools in Oyo State (2011)
The study employed the ex-post factor research type. Sixty Junior Secondary Schools were randomly selected from Ibadan/Ibarapa senatorial district and 40 from Oyo Central. An intact class and all available teachers at the level which consisted of 147 teachers and 2567 students made up the sample. Three instruments: Teaching Effectiveness Questionnaire (TEQ) which was subjected to factors analysis, Students' Attitudes to Social Studies (SASS) and Teacher Questionnaire (TQ) were used to collect data.Data were analysed using descriptive, and multiple regression statistics. Findings indicated that ; over 60% of the social studies teachers in Oyo State junior secondary schools indicated by their students are good in organisation of lessons, assignment and examinations, had mastery of the subject, and are very sensitive to their students' problem. Eleven variables adequately explained the teachers' teaching effectiveness. Students' attitude to social studies, teacher experience, the second subject taught apart from social studies, number of periods of the first subject other than social studies were taught, teacher gender, school location and duration of social studies periods in that order, made significant relative contributions to teaching effectiveness. The listed variables are important predictors of teaching effectiveness that schools need to watch to enhance effective learning and achievement of social studies objectives in the state.